Relevance of book value and earnings: a comparison between islamic and conventional banks in Malaysia / Mohd Halim Kadri. - Kadri, Mohd Halim (Universiti Teknologi MARA Cawangan Selangor, 2016)
This study aimed at investigating the value relevance of book value and earnings of Malaysian Islamic and conventional banks. A market valuation approach was utilised for that purpose. The result of pool sample showed that book value and earnings of Malaysian banks are value relevant. It was also observed that book value and earnings of Islamic and conventional banks are value relevant when they are separated. However, it was found that the explanatory power towards market value provided by Islamic bank is far behind their conventional counterparts. The results implicated that book value and earnings of Islamic banks provide less information content towards market value despite their relevance. This suggests further investigation in future studies. Finally, the study contributes to existing literature in the area of the value relevance of financial information in Malaysia.